The Relationship of Nutrition And Leptin In Cancer - Sarı, Aysel (Çankırı Karatekin Üniversitesi, 2024)
Leptin hormone has an important role in the consumption of excessive food intake and energy expenditure. While leptin acts as a neuroendocrine hormone, it has an important role in metabolic function. Leptin shows peripheral effects on glucose metabolism and gluconeogenesis, and it is aimed to emphasize its importance in its relationship with nutrition. Malnutrition, which is a serious risk for cancer development and progression, also causes bad negative results in many tumor types. Nutritional balance and energy balance are affected at the level of insulin and leptin hormones, and functionality is important on the relationship between nutrition and leptin and cancer. The negative effects on adipose tissue caused by unbalanced nutrition are effective in cancer formation and insulin, insulin resistance, that is, leptin levels. In addition, many studies have reported that unbalanced nutrition tumor damage.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)